Estudo sobre eficiência energética em uma indústria de injeção plástica - Dias, João Paulo Salvador [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The reason of this work is perform a study about using of electrical energy to identify the opportunities through rational use of electrical energy. For that it was necessary perform an analysis of hired energy against consumption. Based in a guide of energy analysis were found the main consumers and verified the main problems, which generate excessive use of electrical energy in a plastic injection factory. It was also analyzed the painting line because there are some thermal equipment that use electrical energy. Based on the data obtained will be proposed ways to reduce the needless consumption and energy use of rationally and efficiently, in addition to re-evaluate the contracted demand based on the new policy of supplying and charging.It were also proposed thermodynamics solutions to reduce the energy consumed in thermal process
Keywords: Energia eletrica - Conservação; Energia eletrica - Consumo; Industria - Consumo de energia; Electric power